Church Involvement In The Tomohon International Flower Festival As An Eco-Theological In The Digitalization Era - Nainggolan, Alon Mandimpu; Heydemans, Nency Aprilia; Manullang, Juanda (Jurnal Teologi Cultivation, 2025)
This article aims to describe the church's involvement in the Tomohon International Flower Festival (TIFF) as an eco-theological action. TIFF 2022 is an annual festival organized by the Tomohon City Government to increase the ecological sensitivity of the church through nature conservation, flower preservation, and improving public welfare. Tomohon City is known as the city of flowers. Therefore, this festival is carried out by the government and supported by the church, and the community to make it a national and international tourist destination. TIFF strategies and impacts have been written about, but what is unique about the findings in this article is that none of the studies describe church involvement through ecotheological studies at TIFF. The use of digital religious practices such as social media or digital apps by churches can increase ecological awareness. This article uses qualitative research methods with data collection techniques, namely observation, interviews, and literature studies. The conclusion of the study is that TIFF 2022 is an appeal to the church to preserve, preserve and be responsible for this nature. The church responded well to TIFF's activities by actively participating in planting flowers both in the yard and in the garden. On the other hand, it needs attention from the younger generation and various parties to plant flowers as an effort to green local wisdom. The TIFF 2022 study uses various fields of contextual theological ecotheology and the discipline of sociology of religion. This research needs to be followed up in the study of environmental ethics, economics, eco-pastoral, environmental education with a broader context to help readers understand TIFF.